2021
DOI: 10.1016/j.heliyon.2021.e06985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health symptoms and its effect on insomnia among healthcare workers who attended hospitals during COVID-19 pandemic: A survey in Dhaka city

Abstract: Background During the COVID-19 pandemic, the high workload, risk of infection, and safety issues for family members may pose a threat to the mental health of healthcare workers (HCWs) working in hospital settings. The study aimed to find out the prevalence of anxiety, depression, and insomnia symptoms were among HCWs, as well as the factors related to these mental health issues. Methods We conducted an online survey of HCWs employed in Dhaka city from June 6 to July 6, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…In respect to gender-based insomnia suffering, female participants are reported at higher risk in this study, which is similar to the prior Bangladeshi studies conducted in the periods of normal [ 29 , 30 ] or pandemic [ 15 , 17 19 ]. Generally, females are highly prone to mental health suffering, a finding that is also consistent with the pandemic-related Bangladeshi studies [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In respect to gender-based insomnia suffering, female participants are reported at higher risk in this study, which is similar to the prior Bangladeshi studies conducted in the periods of normal [ 29 , 30 ] or pandemic [ 15 , 17 19 ]. Generally, females are highly prone to mental health suffering, a finding that is also consistent with the pandemic-related Bangladeshi studies [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, insomnia is associated with a higher level of physical health conditions as per this study findings and reported elsewhere [ 18 ]. Similarly, people with mental health problems like depression, anxiety, suicidality etc., are found as insomniac herein; but none of the prior studies examined the role of suicidality in insomnia [ 14 , 15 , 17 ]. However, the role of these mental health problems in predicting insomnia explanatory power is reported as 12.9%, where other variables (socio-demographics, behavior- and health-related variables, and COVID-19 fear and risk) combinedly explained a total of 18.3% variance of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Most doctors are located in Dhaka and major cities ( 58 ). HCWs working in COVID-19 and non-COVID settings face a high workload, constant exposure, infection risk, ethical decisions about rationing resources among patients, and safety concerns for family members ( 49 , 53 ). As a result, the concerned authority should pay particular attention and care to vaccinated HCWs from urban areas during this or future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Individual economic loss, economic hardship, or economic threat was significantly associated with mental health ( Ali et al, 2021 ). The pandemic has led to increased risks of depression, anxiety, stress, despair ( Pettinicchio et al, 2021 ), insomnia ( Hossain and Ali, 2021 ), and other common mental health problems. The negative relationship between economic distress and mental health may be a cumulative process.…”
Section: Conceptual Frameworkmentioning
confidence: 99%